Re-Interpretation of Makkiyah Verses to Improve Moral Guidance: A Case Study of Flexing Attitudes in The Review of The Tafsir Kemenag - Nadia Alisyia Nuri; Kharis Nugroho; Yeti Dahliana; Andri Nirwana AN (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study examines the prevalent social phenomenon of